Are Students' Image of Scientists Affected by Parent and Teacher Factors? A Study on the Contextual Relationship between Students, Teachers, and Parents (Journal of Science Learning, 2026)
For more than half a century, research has been carried out on the image of scientists. The media, textbooks, teachers, parents, and peer influence were assumed to be the basis of the stereotypical image. Empirical evidence regarding teachers' and parents' perceptions of scientists remains insufficient. This study investigated whether teachers’ and parents’ image of scientists affects the students’ image. Participants consisted of students in the 8-11 age group (n = 122), along with parents (n=104) and teachers (n = 82). Drawings collected via the Draw-a-Scientist Test (DAST) were analysed by the Draw-a-Scientist Test Checklist (DAST-C). The results showed that teachers and parents had no significant effect on students' image of scientists. Therefore, the theoretical underpinnings pointing to the origins of the stereotypical image of scientists were not supported in the study.